Theoretical Framework: Factors for Project Success in Oil & Gas Companies & Contractors in Miri, Sarawak, Malaysia - Sylvester, D.; Abdul Rani, Nazatul Shima (Institute of Electrical and Electronics Engineers, Inc, 2010)
The Oil and Gas Industry is a multimillion- dollar industry. The companies which are involved in the Oil and Gas industry are well aware of the cost factor which plays a very critical part in every industry. The aim of the research is to critically identify and evaluate the depth of the Project Management Triangle concept applied in the execution of projects tendered by the Oil and Gas Companies to relevant contractors. A theoretical framework is proposed for the purpose of this research.